Task Cauchy and Carleman Function - Ashurova Zebiniso Raximovna; Juraeva Nodira Yunusovna; Juraeva Umidakhon Yunusalievna (Zien Journals, 2021)
In this paper we discuss the continuation polyharmonic function its values and the values of its normal derivative on the smooth side of S the boundary of the infinite D. Using this integral representation, we obtain some properties of the polyharmonic functions of this class.
Keywords: Cauchy problem; Carleman function; polyharmonic functions; partial derivatives